Comparative study between LMA supreme with I-gel in anaesthetised adult patient on effectiveness and safety - Samel, Sarika A.; Morale, Shrikant S. (International Journal of Research in Medical Sciences, 2017)
Background: Supreme laryngeal mask airway (SLMA) and I-gel airway devices are second generation supraglottic airway devices (SAD) and are good alternatives to intubation during surgeries. The study was conducted with the objective to compare two supraglottic airway devices for ease of insertion, number of attempts of insertion, hemodynamic changes, incidence of adverse effects like regurgitation, lip and dental trauma and post-operative sore throat, dysphagia or hoarseness. Methods: This study was conducted at Topiwala National Medical College and BYL Nair hospital, Mumbai. 80 patients of ASA class 1 and 2 with Mallampati grading 1 and 2, between age group of 18-60 years and with BMI <28kg/m2 were selected for the study. After induction of anesthesia for all the patients, one of SAD (SLMA or I-gel) was inserted randomly and accordingly they are divided into two groups consisting of 40 in each. Insertion parameters, hemodynamic and respiratory parameters were noted. Patients were also observed for any complications for 1 hour and 24 hours postoperatively. Results: Both groups were compared in terms of demographic characteristics, insertion parameters, hemodynamic and respiratory parameters and found no statistically significant differences between them (p>0.05). Postoperatively no significant complications were observed in terms of dental injury, laryngospasm. Complication like sore throat after 1 hour and after 24 hours was comparatively more in I-gel group but difference was not significant at 1 hr (p>0.05). Dysphagia was reported more in SLMA group (8 cases) than I-gel group (1 case) at one hour and the difference was statistically significant (p=0.013). Conclusions: SLMA and I-GEL are better airway management option for patients undergoing short surgical procedures under general anaesthesia.